Endogenous p53 protein generated from wild-type alternatively spliced p53 RNA in mouse epidermal cells. - Kulesz-Martin, M F (1994)
We previously demonstrated that a wild-type alternatively spliced p53 (p53as) RNA exists in mouse cultured cells and normal mouse tissues at approximately 25 to 33% of the level of the major p53 RNA form. The alternative RNA transcript is 96 nucleotides longer than the major transcript as a result of alternative splicing of intron 10 sequences. The protein expected to be generated from the p53as transcript is 9 amino acids shorter than the major p53 protein and has 17 different amino acids at the carboxyl terminus. We report here that p53as protein exists in nontransformed and malignant epidermal cells and is localized to the nucleus. In addition, p53as protein is preferentially expressed during the G2 phase of the cell cycle and in cells with greater than G2 DNA content compared with the major p53 protein, which is preferentially expressed in G1. The p53as immunoreactivity is elevated and shifted to the G1 phase of the cell cycle following actinomycin D treatment of nontransformed cells but not malignant cells. In view of the dimerization and tetramerization of p53 protein which may be necessary for its DNA binding and transcriptional activation activities, the presence of p53as protein in cells has important implications for understanding the physiological function(s) of the p53 gene.